An Assessment of How Communication Technology Helps Online Education: - (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Online education involves different modes ofcommunication that support teaching and learning through various electronictools. The communication technology is the medium through which the educationis imparted and received. The technology has been evolving with time, creatingbetter tools and modes of online education. This has also helped in increasingthe range of online education. Different types of online education areComputer-Based Training, Internet-Based Training or Web-Based Training. Themost common form of online learning involves the computer and data transmissionthrough a network. In order to enhance the reach of online education, academicinstitutions need to hire and train teachers appropriately. The teachers mustbe well aware of the technological tool used for communication and should bewell versed in the subject. They should be confident with using the computerand the internet. In this study the role of communication technology inimparting online education in India will be assessed. The main aim is tohighlight how communication technology helps online education.